MATHEMATICAL MODELING OF HEAT AND MASS TRANSFER FOR STEAM HUMIDIFICATION CAM - Голінко, Ігор Михайлович; Галицька, Ірина Євгенівна; Степаненко, Валентин Юрійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The dynamic model heat-and-mass transfer for the cam of steam moistening is observed. The offered mathematical description of the humidifying cam considers dynamic behavior on the basic channels of perturbation and regulating. The mathematical model can be used by specialist in automation for the analysis and controller tuning of the industrial conditioners.